2018
DOI: 10.1001/jamafacial.2018.0263
|View full text |Cite
|
Sign up to set email alerts
|

Primary vs Secondary Endosseous Implantation After Fibular Free Tissue Reconstruction of the Mandible for Osteoradionecrosis

Abstract: The clinical and financial implications of the timing of dental rehabilitation after a fibula free tissue transfer (FFTT) for osteoradionecrosis (ORN) and osteonecrosis (ON) of the mandible have yet to be established. OBJECTIVE To compare the outcomes of primary implantation vs secondary implantation after FFTT for ORN and ON of the mandible. DESIGN, SETTING, AND PARTICIPANTS A retrospective review was conducted of 23 patients at a single tertiary academic referral center undergoing primary implantation or sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 24 publications
(60 reference statements)
2
14
0
Order By: Relevance
“…This showed that simultaneous dental implant placement in fibula free flap had a high survival rate if the free flap transfer was successful. This is in agreement with other retrospective studies which reported the overall implant survival rate of 95% to 100% with a mean follow‐up ranging from 8 to 71.7 months 6,16‐22 . Noteworthily, five out of 6 studies reporting 100% survival in simultaneous implant placement were for benign disease 6,16‐18,20 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This showed that simultaneous dental implant placement in fibula free flap had a high survival rate if the free flap transfer was successful. This is in agreement with other retrospective studies which reported the overall implant survival rate of 95% to 100% with a mean follow‐up ranging from 8 to 71.7 months 6,16‐22 . Noteworthily, five out of 6 studies reporting 100% survival in simultaneous implant placement were for benign disease 6,16‐18,20 .…”
Section: Discussionsupporting
confidence: 90%
“…Noteworthily, five out of 6 studies reporting 100% survival in simultaneous implant placement were for benign disease 6,16‐18,20 . Two other studies reported the reasons for failed dental implants (6/58 and 2/76, respectively) were due to flap failure and local infection 21,22 …”
Section: Discussionmentioning
confidence: 99%
“…A previous publication found that over half of free flap reconstructions for ORN required the use of the contralateral neck vessels [17] . Similarly, we have found improved free flap survival rates when using contralateral neck vessels [40] .…”
Section: Technical Considerationssupporting
confidence: 67%
“…An example of a 2.0 mm reconstruction bar is shown in Figure 2A. Recent data suggests that reconstruction bar thickness may correlate with overlying soft tissue loss and hardware exposure rates, with a higher incidence of complications as reconstruction bar thickness increases [40] . Another variation in surgical design includes orientation and placement of the soft tissue component.…”
Section: Technical Considerationsmentioning
confidence: 99%
“…Studies have shown excellent outcomes of dental implant placement in the fibula after reconstruction with the fibula free flap [12][13][14][15]. The fibula also supports dental implants, and a skin paddle of the fibula free flap can be used with the bony component to provide the intraoral lining [11,16].…”
Section: Introductionmentioning
confidence: 99%